Analysis of the role of prespore gene expression in the compartmentalization of mother cell-specific gene expression during sporulation of Bacillus subtilis. - Zhang, L (1996)
A hallmark of sporulation of Bacillus subtilis is the formation of two distinct cells by an asymmetric division. The development programs in these two cells involve the compartmentalized activities of sigma E in the larger mother cell and of sigma F in the smaller prespore. Activation of sigma E requires expression of the sigma F-directed gene spoIIR. By immunofluorescence microscopy of a strain containing a spoIIR-lacZ fusion, we have shown that spoIIR is transcribed exclusively in the prespore. By placing spoIIR under the control of PspoIIE, it was possible to express spoIIR before the spore septum was formed. Strains containing the PspoIIE-spoIIR construct activated sigma E only in the mother cell in organisms that underwent the asymmetric sporulation division. Thus, compartmentalization of sigma E activity did not require the compartmentalization of spoIIR expression. Nor did the compartmentalization of sigma E require SpoIIAA, SpoIIAB, sigma F, or sigma F-dependent transcription, all of which are required for prespore-specific gene expression. It is inferred that although sigma F and sigma E direct compartmentalized gene expression, neither of these sigma factors, nor the genes under their control, directs the process of compartmentalization.